3rd Annual Meeting of the Portuguese Association of Energy Economics & 5th Meeting of Environmental and Energy Economics (UMinho Editora, 2021)
Message from the Programme Committee Chair The 3rd Annual Conference of the Portuguese Association of Energy Economics – APEEN and the International Meeting on Energy and Environmental Economics – ME3 took place on the 18-19 October 2018 in Braga, Portugal. The event was hosted by the Universidade do Minho and gathered the contributions of specialists in Energy and Environmental Economics to enrich the debate about the many issues raised by the management of resources and waste. The main topic was Managing Resources and Waste: challenges for Energy and Environmental Economics beyond 2030. ​Natural resources are the keystone in environmental and energy economics. Nowadays, resource management cannot ignore waste, traditionally seen as a by-product of consumption and production decisions, but increasingly recognized as a source of energy or as new type of resource ​The APEEN & ME3 joint conference had over 50 presentations from researchers from all over the world and lively discussions. Some of these presentations are summarized in the short papers compiled in this Book of Proceedings. We are grateful to have had the presence and contribution of the keynote speakers: Maria L. Loureiro (Universidade de Santiago de Compostela) and Martin Brocklehurst (Kempley Green Consultants). Their speeches challenged us now to think of new research and business opportunities beyond 2030. On behalf of the organizing committee, I thank our sponsor, LIPOR, and all presenters for their academic excellence and lively participation. Lígia Pinto, Universidade do Minho Conference website: http://apeen-me3.eeg.uminho.pt